2012
DOI: 10.1175/2011jpo4597.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Semidiurnal Internal Tide Variability in the Southern California Bight

Abstract: The Regional Oceanic Modeling System (ROMS) is applied in a nested configuration with realistic forcing to the Southern California Bight (SCB) to analyze the variability in semidiurnal internal wave generation and propagation. The SCB has a complex topography with supercritical slopes that generate linear internal waves at the forcing frequency. The model predicts the observed barotropic and baroclinic tides reasonably well, although the observed baroclinic tides feature slightly larger amplitudes. The stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 44 publications
7
69
0
Order By: Relevance
“…In the case of the south, where the topography was subcritical (g/c < 1) and the first mode was dominant, it appears that the baroclinic energy generated on the shelf break or the Biobío canyon should propagate toward the coast. Therefore, our observational results for Coquimbo and Concepcion resemble theoretical cases studied by Muller and Liu [2000] and Buijsman et al [2012].…”
Section: Baroclinic Semidiurnal Tidal Currentssupporting
confidence: 79%
See 1 more Smart Citation
“…In the case of the south, where the topography was subcritical (g/c < 1) and the first mode was dominant, it appears that the baroclinic energy generated on the shelf break or the Biobío canyon should propagate toward the coast. Therefore, our observational results for Coquimbo and Concepcion resemble theoretical cases studied by Muller and Liu [2000] and Buijsman et al [2012].…”
Section: Baroclinic Semidiurnal Tidal Currentssupporting
confidence: 79%
“…In the case of Coquimbo, the fluctuations were not only associated with the first dynamic mode but also with the second and third modes. Buijsman et al [2012], using a numerical model in the Southern California Bight, showed that the energy of semidiurnal internal waves generated over the continental slope was reflected toward the ocean. Some energy associated with high mode-numbers, however, propagated toward the coast when the topography was supercritical (ratio of slope bathymetry (g) and slope internal waves (c) is higher than 1, g/c > 1).…”
Section: Baroclinic Semidiurnal Tidal Currentsmentioning
confidence: 99%
“…Baroclinic tides are primarily oriented in the horizontal direction and arises almost entirely from gradients in the hydrostatic pressure (Carter et al, ). As a result, the hydrostatic ROMS has been widely utilized for regional ocean baroclinic tidal modeling (Buijsman et al, ; Dunphy et al, ; Powell et al, ; Robertson, , ; Robertson & Ffield, ; Xu, Liu, et al, ). Because of the implicit diffusion in the upstream‐biased advection scheme, the explicit lateral viscosity and diffusivity are null everywhere in the current model, except in the sponge layers near the open boundaries, where they increase smoothly on a few grid points.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Over the deep OR continental slope, Kelly et al (2012) find significant internal tide generation from along-slope currents interacting with along-slope topographic variations, leading to strong gradients in F E over the 10-km scales that characterize the underlying topographic variability. In semienclosed basins, the refraction, reflection, and scattering of internal tide energy can work to create resonances or basin-scale modes (e.g., Buijsman et al 2012) that alter the resultant wavefield (Guo et al 2011). …”
Section: Relating Nliw Occurrence To Shelfbreak Dynamicsmentioning
confidence: 99%